2010
DOI: 10.1101/gr.102921.109
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of heterozygous mutations in Drosophila melanogaster using genomic capture sequencing

Abstract: One of the key advantages of using Drosophila melanogaster as a genetic model organism is the ability to conduct saturation mutagenesis screens to identify genes and pathways underlying a given phenotype. Despite the large number of genetic tools developed to facilitate downstream cloning of mutations obtained from such screens, the current procedure remains labor intensive, time consuming, and costly. To address this issue, we designed an efficient strategy for rapid identification of heterozygous mutations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Previous use of NGS in targeted gene cloning has focused on model organisms [ e.g. , A. thaliana (Mokry et al 2011; Uchida et al 2011; Austin et al 2011), Drosophila melanogaster (Blumenstiel et al 2009; Wang et al 2010), Caenorhabditis elegans (Sarin et al 2008), and fission yeast (Irvine et al 2009)]. Sorghum, while sequenced (Paterson et al 2009), has not been used successfully to clone genes using NGS tools.…”
Section: Discussionmentioning
confidence: 99%
“…Previous use of NGS in targeted gene cloning has focused on model organisms [ e.g. , A. thaliana (Mokry et al 2011; Uchida et al 2011; Austin et al 2011), Drosophila melanogaster (Blumenstiel et al 2009; Wang et al 2010), Caenorhabditis elegans (Sarin et al 2008), and fission yeast (Irvine et al 2009)]. Sorghum, while sequenced (Paterson et al 2009), has not been used successfully to clone genes using NGS tools.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most other mutagens, the molecular lesions caused by EMS are essentially random, ensuring that most genes of interest will be targeted and that multiple lesions will be found in each gene. Whole genome sequencing now allow us to reliably and efficiently map EMS induced lesions at very reasonable costs (Blumenstiel et al, 2009;Wang et al, 2010) (H.J.B., unpublished data).…”
Section: : Forward Genetic Approaches To Isolate Novel Neuronal Genesmentioning
confidence: 99%
“…In parallel with its medical applications, targeted capture began to emerge as a powerful approach to address evolutionary questions in humans (Briggs et al 2009; Burbano et al 2010; Krause et al 2010; Li et al 2010; Yi et al 2010). Although initially restricted to species with sequenced genomes (e.g., chimpanzee, Perry et al 2010; Drosophila melanogaster , Wang et al 2010; maize, Fu et al 2010), more recent extensions to non-reference species have demonstrated the potential to effectively use targeted capture across diverse taxa (Cosart et al 2011; Mason et al 2011; Vallender 2011; Bi et al , 2012, 2013; Good et al 2015). Nonetheless, targeted capture remains relatively uncommon in evolutionary biology studies.…”
Section: Introductionmentioning
confidence: 99%